Improving work performance among academic staff through transformational leadership: a conceptual analysis - Kang, Lulu; Abdul Aziz, Nor Azni; Che Hassan, Norlizah (Macrothink Institute, 2023)
Transformational leadership has become necessary in management practices. In people-oriented organizations, the overall performance may largely depend on leadership styles. Although a variety of studies have provided the possibility for a positive connection between transformational leadership and work performance, the advantages of transformational leadership in educational settings need to be further analyzed. Transformational leadership was shown to be effective in predicting various variables, including work performance, in different contexts. Transformational leaders in colleges and universities are able to motivate the lecturers to go beyond expectations in pursuit of the vision of higher educational institutions. However, there is still a shortage of studies conducted at higher educational institutions. It is essential to examine the effectiveness of transformational leadership to align lecturers’ behaviors with the goals of higher educational institutions. Under the social exchange theory, this paper reviews the connection between transformational leadership and work performance among academic staff at higher institutions. The implication of transformational leaders toward improving and maintaining a positive work environment is discussed.